The Implementation of the Prosecutor's Code of Ethics after the issuance of Attorney General Regulation Number 4 of 2024 on the Professionalism and Integrity of Public Prosecutors in Criminal Trials - Ester Olivia Lase; Sigar P. Berutu (Ekasakti Journal of Law and Justice, 2026)
The prosecutor as the public prosecutor plays an important role in realizing a fair, honest, and authoritative criminal justice. The magnitude of this responsibility prompted the Prosecutor's Office of the Republic of Indonesia to issue Prosecutor's Regulation Number 4 of 2024 concerning the Prosecutor's Code of Conduct to strengthen the ethical foundation of the prosecutor's profession more comprehensively. The presence of this regulation is an important instrument in fostering prosecutors' behavior, especially in the implementation of prosecution duties in criminal trials. This research is a normative legal research with a statutory and conceptual approach that uses primary legal materials in the form of PERJA Number 4 of 2024, the Prosecutor's Law, and the Criminal Procedure Code. The results of the study show that the regulation brings normative updates in the regulation of the prosecutor's code of conduct. However, its implementation in the field still faces various challenges, including inconsistency in sanctions enforcement, weak supervision mechanisms, and limited continuous ethical coaching, so that the implementation of the code of conduct has not been fully optimal in strengthening the professionalism and integrity of prosecutors in criminal trials.